1993
DOI: 10.1128/jvi.67.3.1405-1413.1993
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of structural proteins during late events in the life cycle of polyomavirus

Abstract: The polyomavirus minor late capsid antigen, VP2, is myristylated on its N-terminal glycine, this modification being required for efficient infection of mouse cells. To study further the functions of this antigen, as well as those of the other minor late antigen, VP3, recombinant baculoviruses carrying genes for VP1, VP2, and VP3 have been constructed and the corresponding proteins have been synthesized in insect cells. A monoclonal antibody recognizing VP1, a-PyVP1-A, and two monoclonal antibodies against the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 41 publications
6
68
0
Order By: Relevance
“…The proteins with EGFP in the opposite orientation (EGFP-VP2, EGFP-VP3) were targeted preferentially into the cell nucleus, and had markedly lower affinity to intracellular membranes. In agreement with our results, previous studies have shown that minor proteins were not targeted efficiently into the nucleus in insect cells or in African Green monkey kidney cells when VP1 was not co-expressed [8,9].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The proteins with EGFP in the opposite orientation (EGFP-VP2, EGFP-VP3) were targeted preferentially into the cell nucleus, and had markedly lower affinity to intracellular membranes. In agreement with our results, previous studies have shown that minor proteins were not targeted efficiently into the nucleus in insect cells or in African Green monkey kidney cells when VP1 was not co-expressed [8,9].…”
Section: Discussionsupporting
confidence: 93%
“…During MPyV infection, newly synthesized structural proteins form complexes (5VP1-1VP2, or 5VP1-1VP3) in the cytoplasm, which are then transported into the cell nucleus [8,9,19]. In the absence of VP1, we found that a substantial amount of VP2 or VP3 in the cytoplasm was co-localized with intracellular membranes, similar to the observation with fusion variants where EGFP was connected to their C-termini (VP2-EGFP, VP3-EGFP).…”
Section: Discussionsupporting
confidence: 83%
“…Cells were harvested 72 h post infection (p.i. ), lysed, and VLPs were purified by CsCl and sucrose gradients as described previously [8].…”
Section: Isolation Of Capsid-like Particles From Insect Cellsmentioning
confidence: 99%
“…The recombinant plasmid p425GVP1 wt (kindly provided by Mgr. L. Synek (Charles University, Prague, Czech Republic)) and p426GVP1 wt was constructed by ligation of a BamHI-BglII fragment containing the VP1 gene cut from pVL1393-VP1 [13] and yeast shuttle expression vector p425G or p426G [24] cut with BamHI.…”
Section: Preparation Of Recombinant Plasmidsmentioning
confidence: 99%